2013
DOI: 10.1093/ejcts/ezt565
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of video-assisted thoracoscopic segmentectomy using infrared thoracoscopy with indocyanine green

Abstract: VATS segmentectomy using IRT with ICG allows the maintenance of a clear surgical view and identification of the intersegmental line in a high proportion of cases. Therefore, we consider this method to be useful for minimally invasive thoracic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 19 publications
3
86
0
4
Order By: Relevance
“…In our study, the ISP was not accurately identified in 12% of patients. This result is quite similar to that of Tarumi et al (15%) (9). The collateral vascularization between the pulmonary and bronchial circulation could explain this result.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the ISP was not accurately identified in 12% of patients. This result is quite similar to that of Tarumi et al (15%) (9). The collateral vascularization between the pulmonary and bronchial circulation could explain this result.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the surgeon needs intraoperative assistance to identify the ISP. As previously described, near-infrared angiography with indocyanine green (ICG) can be helpful in the identification of the ISP during VATS (7)(8)(9). In contrast to bronchial segmentation, vascular segmentation with ICG is easier and can enable precise anatomical resection.…”
Section: Introductionmentioning
confidence: 99%
“…According to other toxicity studies, intravenous injection of up to 5.0 mg/kg ICG is quite safe and acceptable (9). In the present study, the sensitivity of this ICG system was better than that of previous reports, so we were able to create ICGF images twice in one operation (8,10). For example, when we performed right segments (S)9+10 segmentectomy, we first divided the intersegmental line between S6 and the basal segments along the ICGF demarcation after clamping the pulmonary artery of S6.…”
Section: Discussionmentioning
confidence: 76%
“…In 2010, Misaki et al observed a welldefined color zonation in all patients (n=8) who underwent thoracotomy and discussed that they have developed a new clinically applicable method for visualizing adjacent lung segments based on blood supply and with the use of ICG with infrared thoracoscopy (5). They expanded this technique to 44 patients (thoracotomy in 31 and videoassisted TS or VATS in 13) (8). In 2014, Tarumi et al additionally used infrared thoracoscopy with ICG during VATS segmentectomy and reported that the identification of the intersegmental line based on blood flow differences was possible in 11/13 (84.6%) patients after the dissection of hilar structures (8).…”
Section: Discussionmentioning
confidence: 99%
“…They expanded this technique to 44 patients (thoracotomy in 31 and videoassisted TS or VATS in 13) (8). In 2014, Tarumi et al additionally used infrared thoracoscopy with ICG during VATS segmentectomy and reported that the identification of the intersegmental line based on blood flow differences was possible in 11/13 (84.6%) patients after the dissection of hilar structures (8). In another study in 2013, Kasai et al observed that infrared thoracoscopy with ICG by 1-or 2-wavelength methods was useful for detecting the intersegmental line, facilitating anatomical segmentectomy in 30 consecutive patients (9).…”
Section: Discussionmentioning
confidence: 99%